Great Powers' National Security Strategy towards International System's Shift: The Case of the United States and Russian Federation” - Aqeel, Wasfi (Dirasat: Human and Social Sciences, 2022)
This research discusses the national security strategy of the United States of America and the Russian Federation according to international changes between 2000 and 2020. The study proposed a shift in the national security strategies from the strongest nation concept to the global cooperation and collaboration principles. This modification was due to the change in the structure and values of the international system, Therefore, this study uses the Principles of New Realism, Using the international system approach to clarify the nature of the new entries in it. This study concluded that the United States and Russia still depend the realistic on the superior nation principle when making national security decisions. despite the claim of nations’supremacy of liberal values based on international cooperation and integration, which appeared in their international behavior.